Method for reducing aluminum alloy heat loss in high pressure die casting shot sleeves. (3rd September 2018) - Okayasu, M.; Wu, S.; Hirayama, T.; Lee, Y.-S.
ABSTRACT: To reduce the amount of casting defects in diecast components, a new shot-sleeve is proposed. Cold flakes are generated by solidification of the casting material in the shot-sleeve before the injection process. To solve this problem, a thermal insulation system is introduced on the inner shot-sleeve surface, with tiny grooves being machined to create an air gap between the melt and the sleeve surface. Various casting materials with different material properties are used to examine the insulating effect of the shot-sleeve. The degree of thermal insulation is found to be influenced by the material properties, with the surface tension being significant factors. This thermal insulation effect allows the production of high-quality samples and therefore with good mechanical properties. When casting materials with low surface tension are used, the melt is able to penetrate deeply into the grooves of the shot-sleeve, lessening the insulation effect and leading to the defect.